(untitled) (Journal of Faculty of Education, 2021)
Umayyad rule supportive poerty in "tarikhAtabari" prepared by Dr.Suliman Abdalla & Dr. Faiza Ali Awadaleem. This study aimd to show the styles that were used by poets to Support "BaniUmayah state" in the book "the history of messengers and prophets" for Altabari. This book was chosen because of its mach poetry that was cited by the auther،hence its worth study. This study yielded many results،the most important of which. The poetry eited by Altabari to support Umayyad Rule is not all that is said in this term،but he missed a lot of poetry that is made in " Dawaween" of the poets of this era and the other compositions. The poets that the author cited their poetry come from different backgrounds such as the center of the state " Alsham and Iraq" state suburbs khurasan and Beyond.The pets motive was to compose supportive poetry for Umayyad rule using different styles in the different genres praising sati ring،congratulating،tribal poetry and the talksabout Islamic conquests،and finally qutaybah Bin Muslim is regarded as the only one leader who was praised among the others in the poetry that support the state،and that the was satirized for his state disobedience.